STIGMA MASYARAKAT SUKU BANJAR TERHADAP ORANG DENGAN GANGGUAN JIWA BERAT DI MASA PANDEMI COVID-19 - lanawati lanawati; Gertrudis Tutpai; Dewi Sinta (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2022)
Negative stigma related to mental disorders is still found in many people in Indonesia. The existence of this stigma can have a negative impact on people with mental disorders, families, and society. So it has the potential to affect the rehabilitation process in the community. This study aims to describe the stigma of the Banjarese community related to people with mental illness, especially during the Covid-19 pandemic. Using quantitative descriptive research design. Data were collected using a questionnaire on 30 respondents and analyzed using a frequency distribution. This study found that 63.3% of the Banjarese involved in this study had a negative stigma toward severe people with mental illness. Where there is an assumption that the cause of mental disorders is still supernatural, perceptions related to people with mental illness can range in any situation. People with mental illness are also considered not to have the ability to work and socialize, and the primary treatment is religious treatment. From these findings, it is crucial for primary health services to optimize health promotion and provide information related to mental disorders and the treatment process, to increase public knowledge so as to reduce the negative stigma on mental disorders.